2015
DOI: 10.1016/j.eats.2015.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Anatomic Coracoclavicular Ligament Repair Using a 6-Strand Polyester Suture Tape and Cortical Button Construct

Abstract: Acromioclavicular separations are common injuries. Low-grade separations are typically managed with nonoperative treatment. However, surgical treatment is recommended for high-grade separations, as well as for chronic low-grade separations that remain symptomatic. Multiple fixation techniques have been described over the past several decades, including Kirschner wires, hook plates, and coracoclavicular screws. More recently, a single-tunnel suture-graft repair and an anatomic reconstruction reproducing both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…It should be kept in mind that all described arthroscopic techniques have reported pitfalls, including implant migration, need for implant removal, failure of reduction and fracture of coracoid and clavicle. 32 …”
Section: Arthroscopic Techniquementioning
confidence: 99%
“…It should be kept in mind that all described arthroscopic techniques have reported pitfalls, including implant migration, need for implant removal, failure of reduction and fracture of coracoid and clavicle. 32 …”
Section: Arthroscopic Techniquementioning
confidence: 99%
“…Typical open surgery methods include the Phemister method 14 or Neviaser method 11 to repair the acromioclavicular ligament, the Bosworth method 5 for inter-coracoclavicular fixation, the Weaver-Dunn method 25 or Cadenat method 6 using the coracoacromial ligament as a substitute ligament for the coracoclavicular ligament, and the Dewar method 8 for treatment by dynamic stabilization with the conjoined tendon. In contrast, Salzmann et al, 16 Scheibel et al, 17 Balog et al, 2 De Beer et al, 7 and Takase and Yamamoto 21 have reported methods for anatomically reconstructing the trapezoid and conoid ligaments with arthroscopic surgery. Furthermore, Scheibel et al reported that posterior instability of the ACJ may remain with vertical stabilization alone and it is important to reconstruct the acromioclavicular ligament simultaneously, which reduces posterior instability.…”
Section: Discussionmentioning
confidence: 99%
“…10 There are multiple open and arthroscopic-assisted methods for fixation now available for higher grade separations or chronic grade III separations that produce good clinical results that are lasting. [11][12][13][14] Overall, conservative treatment is recommended for lower grade (I, II) separations, early operative treatment is recommended for higher grade (IV-VI) separations and no definitive management of grade III injuries is universally agreed upon. 15 The efficacy of weighted AC joint radiographs has been evaluated previously.…”
Section: Discussionmentioning
confidence: 99%